Reversal of overdose on fentanyl being illicitly sold as heroin with naloxone nasal spray: A case report. (3rd June 2015) - Fareed, Ayman; Buchanan‐Cummings, Ann Marie; Crampton, Kelli; Grant, Angela; Drexler, Karen
<x xml:space="preserve">Abstract</x> Background This is a case report describing a reversal of fentanyl overdose with naloxone nasal spray. The patient was not aware that he overdosed on fentanyl being sold as heroin. Methods The Veterans Health Administration (VHA) has implemented an initiative to provide education for veterans, their families, friends and significant others about opioid overdose and use of naloxone reversal kits. The Atlanta VA Medical Center adopted this program to reduce the risk of opioid overdose in high risk patients. Results Over the past year, we provided educational sessions for 63 veterans and their families. We also prescribed 41 naloxone kits. We have received three reports of opioid overdose reversal with use of naloxone kits prescribed by the Atlanta VA Medical Center. Conclusions and Scientific significance The authors recommend that public health administrators and policy makers advocate for the implementation of these programs to reduce the rising number of overdose death in the United States and worldwide. (Am J Addict 2015;24:388 –390)